Unreal engine, game development from A to Z : develop fantastic games and solve common development problems with Unreal Engine 4 : a course in three modules.: develop fantastic games and solve common development problems with Unreal Engine 4 : a course in three modules. (2016) - Lee, Joanna; Doran, John P, 1988 or 1989-; Misra, Nitish
No abstract available